The Location of Experience - Pinch, Adela (Fordham University Press, 2025)
We tend to feel that works of fiction give us special access to lived experience. But how do novels cultivate that feeling? Where exactly does experience reside? The Location of Experience argues that, paradoxically, novels create experience for us not by bringing reality up close, but by engineering environments in which we feel constrained from acting. By excavating the history of the rise of experience as an important category of Victorian intellectual life, this book reveals how experience was surprisingly tied to emotions of remorse and regret for some of the era’s great women novelists: the Brontës, George Eliot, Margaret Oliphant, and Elizabeth Gaskell. It shows how these writers passed ideas about experience—and experiences themselves—among each other.Drawing on intellectual history, psychology, and moral philosophy, The Location of Experience shows that, through manipulating the psychological dimensions of fiction’s formal features, Victorian women novelists produced a philosophical account of experience that rivaled and complemented that of the male philosophers of the period.The Location of Experience: Victorian Women Writers, the Novel, and the Feeling of Living is available from the Knowledge Unlatched on an open-access basis.